Mitochondrial Quality Control in Aging and Heart Failure: Influence of Ketone Bodies and Mitofusin-Stabilizing Peptides - Thai, Phung N.; Seidlmayer, Lea K.; Miller, Charles; Ferrero, Maura; Dorn, Gerald W.; Schaefer, Saul; Bers, Donald M.; Dedkova, Elena N. (Frontiers in Physiology, 2019)
Aim: Mitochondrial function declines with age, and progressive mitochondrial damage may impair cellular function and contribute to heart failure (HF) development. Proper removal of damaged mitochondria (mitophagy) is essential for cardiovascular health, and is affected by metabolic substrates and nutrient depriviation. HF has metabolic similarities to starvation where increased formation and consumption of ketone bodies (KBs) is observed. Here, we tested the hypothesis that KBs contribute to activation of mitophagy in aging and HF. Methods: We assessed mitophagy by measuring mitochondrial Parkin accumulation and LC3-mediated autophagosome formation in cardiomyocytes from young (2.5 months), aged (2.5 years) and rabbits with HF (2.5 years) induced by aortic insufficiency and stenosis. Levels of reactive oxygen species (ROS) generation and redox balance were monitored using genetically encoded sensors ORP1-roGFP and GRX1-roGFP, targeted to mitochondrial or cytosolic compartments. Results: Young rabbits exhibited limited mitochondrial Parkin accumulation with small ( 1 µm2) puncta. Those small Parkin puncta increased 4-fold in aged rabbit hearts, accompanied by elevated LC3-mediated autophagosome formation. HF hearts exhibited fewer small puncta, but many very large Parkin-rich regions (4-5 µm2) with completely depolarized mitochondria. Parkin protein expresson was barely detectable in young, much higher in aged and maximal in HF hearts. Mitofusin 2 (MFN2) expression was reduced by almost 50% in HF, consistent with improper fusion-fission contributing to mitochondrial Parkin build-up. The ketone body β–hydroxybutyrate (β-OHB) enhanced mitophagic flux in young and aging myocytes, but not in HF where β-OHB further increased the number of cells with giant Parkin-rich fusions. This β-OHB effect on Parkin-rich areas was prevented by cell-permeant TAT-MP1Gly peptide (thought to promote MFN2-dependent fusion). Mitochondrial ROS was highest in HF and partially decreased by β-OHB. However, basal cytosolic ROS was highest in aged myocytes and lower in HF (but β-OHB partially restored ROS). We suggest that basal cytosolic ROS could serve as a signal to activate Parkin recruitment to the mitochondria. Conclusion: We conclude that elevated ketone body levels are beneficial for mitochondrial repair in the aging heart. However impaired MFN2-mediated fusion-fission process in HF reduces this benefit, as well as Parkin degradation and mitophagic flux.